Pengaruh Edukasi Anemia dengan Model PAKEM terhadap Tingkat Pengetahuan dan Kepatuhan Konsumsi Tablet Tambah Darah pada Remaja Putri di SMK Negeri 2 Padang - Iis Dahlia; Masrul Masrul; Arni Amir (Universitas Hang Tuah Pekanbaru, 2026)
Anemia is a global health problem with significant impacts on adolescent girls. The prevalence of anemia among women aged ≥15 years worldwide remains stagnant at 29.9%. Compliance with iron tablet consumption remains low, partly due to inadequate knowledge. The Participatory, Active, Creative, Effective, and Fun (PAKEM) education model is considered a potential approach to improve knowledge and promote compliance with iron tablet consumption. This study aimed to analyze the effect of PAKEM-based anemia education on knowledge levels and compliance with iron tablet consumption among adolescent girls at SMK Negeri 2 Padang. This study employed a quasi-experimental design with a pretest–posttest control group approach. The research was conducted from May to October 2025, involving 74 adolescent girls, who were divided into intervention and control groups using simple random sampling. Data were collected using a knowledge questionnaire and the Morisky Medication Adherence Scale (MMAS-8). Univariate data were presented as frequency distributions, while bivariate analysis was performed using the chi-square test with a significance level of p<0.05. The results showed an increase in knowledge in the intervention group, from predominantly moderate (48.6%) to good (73.0%). Compliance with iron tablet consumption improved from predominantly low (64.9%) to moderate (43.2%) after receiving PAKEM-based education. The chi-square test showed significant differences in knowledge (p=0.001) and compliance with iron tablet consumption (p=0.008) between the intervention and control groups after receiving PAKEM-based anemia education.). In conclusion, PAKEM-based anemia education is effective in improving knowledge and compliance with iron tablet consumption among adolescent girls. This model can be recommended as an innovative strategy to enhance anemia prevention programs in schools.